Α‐Conotoxins active at α3‐containing nicotinic acetylcholine receptors and their molecular determinants for selective inhibition. (11th June 2017) - Cuny, Hartmut; Yu, Rilei; Tae, Han‐Shen; Kompella, Shiva N; Adams, David J
Abstract : Neuronal α3‐containing nicotinic acetylcholine receptors (nAChRs) in the peripheral nervous system (PNS) and non‐neuronal tissues are implicated in a number of severe disease conditions ranging from cancer to cardiovascular diseases and chronic pain. However, despite the physiological characterization of mouse models and cell lines, the precise pathophysiology of nAChRs outside the CNS remains not well understood, in part because there is a lack of subtype‐selective antagonists. α‐Conotoxins isolated from cone snail venom exhibit characteristic individual selectivity profiles for nAChRs and, therefore, are excellent tools to study the determinants for nAChR‐antagonist interactions. Given that human α3β4 subtype selective α‐conotoxins are scarce and this is a major nAChR subtype in the PNS, the design of new peptides targeting this nAChR subtype is desirable. Recent studies using α‐conotoxins RegIIA and AuIB, in combination with nAChR site‐directed mutagenesis and computational modelling, have shed light onto specific nAChR residues, which determine the selectivity of the α‐conotoxins for the human α3β2 and α3β4 subtypes. Publications describing the selectivity profile and binding sites of other α‐conotoxins confirm that subtype‐selective nAChR antagonists often work through common mechanisms by interacting with the same structural components and sites on the receptor. Linked Articles: This article is part of a themed section on Nicotinic Acetylcholine Receptors. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.11/issuetoc